2007
DOI: 10.1128/iai.01508-06
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Pattern in Human Brain Endothelial Cells in Response to Neisseria meningitidis

Abstract: To extend our knowledge of target proteins in endothelial cells infected with the meningitis-causing pathogen Neisseria meningitidis, we characterized the interaction between the bacterial and human brain microvascular endothelial cell (HBMEC) monolayers. By use of human cDNA microarrays, transcriptional analysis revealed distinct responses to 4 and 8 h of infection. We also addressed the question of whether the major virulence factor of meningococci, i.e., the capsule, influences the host cell response. Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 69 publications
4
41
0
Order By: Relevance
“…This response was dependent on the GBS b-h/c toxin, the transcriptional regulator of virulence, CovR and PilA expression (Doran et al 2003;Lembo et al 2010;Banerjee et al 2011). Additional in vitro studies with S. pneumoniae, HiB, S. typhimurium, E. coli K1, Streptococcus suis, L. monocytogenes, and N. meningitidis reveal a similar core BMEC transcriptional response that results in the induction of neutrophil signaling pathways (Wilson and Drevets 1998;Vadeboncoeur et al 2003;Galanakis et al 2006;Schubert-Unkmeir et al 2007;Banerjee et al 2010;van Sorge et al 2011). Continued exposure and invasion of the pathogen may result in overactivation of BBB endothelium and lead to increased inflammation that may ultimately compromise BBB integrity.…”
Section: Inflammation and Bbb Permeabilitymentioning
confidence: 96%
“…This response was dependent on the GBS b-h/c toxin, the transcriptional regulator of virulence, CovR and PilA expression (Doran et al 2003;Lembo et al 2010;Banerjee et al 2011). Additional in vitro studies with S. pneumoniae, HiB, S. typhimurium, E. coli K1, Streptococcus suis, L. monocytogenes, and N. meningitidis reveal a similar core BMEC transcriptional response that results in the induction of neutrophil signaling pathways (Wilson and Drevets 1998;Vadeboncoeur et al 2003;Galanakis et al 2006;Schubert-Unkmeir et al 2007;Banerjee et al 2010;van Sorge et al 2011). Continued exposure and invasion of the pathogen may result in overactivation of BBB endothelium and lead to increased inflammation that may ultimately compromise BBB integrity.…”
Section: Inflammation and Bbb Permeabilitymentioning
confidence: 96%
“…Interestingly, studies of the brain endothelium challenged with the encapsulated bacterium Neisseria meningitidis revealed changes in the expression of genes encoding cytoskeletal proteins, likely indicating a similar reorganization of the cytoskeleton as observed with C. neoformans (45). N. meningitidis is a common cause of bacterial meningitis, and disruption of the BBB is a hallmark event in this disease (45).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have demonstrated that the expression of certain meningococcal outer membrane components is regulated upon contact with the host epithelium, thereby facilitating meningococcal colonization (6,33). In a proteomic analysis, we identified several meningococcal proteins whose expression was upregulated in bacteria attached to host cells compared to their levels in bacteria alone (unpublished results).…”
Section: Resultsmentioning
confidence: 95%